Dialog Kemanusiaan: Mengupayakan Dialog antara Spiritualitas Trinitaris dengan Ateisme Spiritual ala André-Comte Sponville - Fiktor Banoet (Asosiasi Teolog Indonesia, 2020)
Is there room for furthering a humanistic dialogue on the interplay between Christianity and atheism? Whence an opportunity for investigating the discursive, practical, and even subtle relations between the spiritualities of these ir/religious domains? In this article, I explore these imaginative possibilities following my conviction that any efforts to bridge such humanistic dialogue between Christian and atheist spiritualities are to be sustained by taking a position of paradox—namely, within a “spiritual” zone of commensurability and incommensurability that determines the conditions (and limits) for any comparative or correlative work. This thesis emerges from a consideration of André Comte-Sponville’s efforts to develop a discourse à la “spirituality without God.” Utilizing a critical approach, I frame spirituality without God as a shared discourse, that is, a discursivity under construction between a cosmic spirituality on the one hand and a dialogically humanistic perspective on the other. The direction and benefit of this tandem construction is having the room to experience a Trinitarian spirituality, a possibility and opportunity that emerges after taking into dialogical consideration the critical message that an atheistic spirituality puts toward the task of theology in the midst of so many humanitarian (in addition to ecological) crises. Such discursive correspondence is a matter of contemporary historical import, particularly in the Indonesian context marked by violence and socioreligious dysfunction.